Splenectomy Improves Hemostatic and Liver Functions in Hepatosplenic Schistosomiasis Mansoni. - Luiz Arthur Calheiros Leite; Adenor Almeida Pimenta Filho; Rita de Cássia dos Santos Ferreira; Caíque Silveira Martins da Fonseca; Bianka Santana dos Santos; Silvia Maria Lucena Montenegro; Edmundo Pessoa de Almeida Lopes; Ana Lúcia Coutinho Domingues; James Stuart Owen; Vera Lucia de Menezes Lima (PLoS ONE, 2015)
Schistosomiasis mansoni is a chronic liver disease, in which some patients (5-10%) progress to the most severe form, hepatosplenic schistosomiasis. This form is associated with portal hypertension and splenomegaly, and often episodes of gastrointestinal bleeding, even with liver function preserved. Splenectomy is a validated procedure to reduce portal hypertension following digestive bleeding. Here, we evaluate beneficial effects of splenectomy on blood coagulation factors and liver function tests in hepatosplenic schistosomiasis mansoni compared to non-operated patients.Forty-five patients who had undergone splenectomy surgery were assessed by laboratory analyses and ultrasound examination and compared to a non-operated group (n = 55). Blood samples were obtained for liver function tests, platelet count and prothrombin time. Coagulation factors (II, VII, VIII, IX and X), protein C and antithrombin IIa, plasminogen activator inhibitor-1 were measured by routine photometric, chromogenic or enzyme-linked immunosorbent assays, while hyperfibrinolysis was defined by plasminogen activator inhibitor-1 levels. Both groups had similar age, gender and pattern of periportal fibrosis. Splenectomized patients showed significant reductions in portal vein diameter, alkaline phosphatase and bilirubin levels compared to non-operated patients, while for coagulation factors there were significant improvement in prothrombin, partial thromboplastin times and higher levels of factor VII, VIII, IX, X, protein C and plasminogen activator inhibitor-1.This study shows that the decrease of flow pressure in portal circulation after splenectomy restores the capacity of hepatocyte synthesis, especially on the factor VII and protein C levels, and these findings suggest that portal hypertension in patients with hepatosplenic schistosomiasis influences liver functioning and the blood coagulation status.